Pengaruh Ukuran Perusahaan, Kinerja keuangan dan Eksposur Media Pada Tingkat Pengungkapan Lingkungan - Hadjoh, Rinny Amelia; Sukarta, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.No.07.Tahun 2013, 2013)
The tendency of companies use technology increasing for achieving its high performance . Impact on using of technology that have a significant effect on the pollution damage to the environment . Role of the media in this case is important to control to the running of  company. The purpose of this study is to examine and obtain empirical evidence of the influence of firm size , financial performance and media exposure on the disclosure of environmental information in their annual reports . Sampling technique which used in this study were stratified random sampling and obtained 30 samples of firms with one hundred and fifty observations over the years 2006-2010 . The analysis technique is multiple linear regression . The result of analysis describe the size of company measured by the natural logarithm of total assets and the company's financial performance has a positive effect on environmental disclosure at annual reports . On the other hand the media exposure variable has no effect on environmental disclosures at annual reports.
Keywords: environmental disclosure, firm size, financial performance, media exposure